ELEMENTARY/MIDDLE SCHOOL TEACHERS' UNDERSTANDING OF SEX EDUCATION BASED ON LIVING VALUE EDUCATION (LVE) IN YOGYAKARTA - Apriani, An-Nisa; Putri, Mufida Awalia; Heksaputra, Dadang; Wijaya, Dhina Puspasari; Emiliana, Emiliana; Ramadan, Muchammad Ilham Rahmad (PD PGMI se Indonesia, 2024)
Teachers' understanding of sex education and its implementation in learning is very important for primary school students. Teachers should know about the knowledge and attitude towards what sex education is and how it is implemented. The purpose of this study was to reveal teachers' knowledge about sex education based on Living Value Education (LVE) and implement it in learning sex education. This research method is descriptive survey type for exploratory or exploratory purposes. The data collection technique uses a questionnaire in the form of a google form. The questionnaire in this case includes teachers' understanding of LVE-based sex education in accordance with the validated grids. The population of this study included all primary school level teachers in DIY Province. The sample technique selected using Purposive sampling. The research subjects who constituted the research sample were 248 teachers consisting of class teachers, subject teachers, and co-curricular teachers of elementary schools and madrasah ibtidaiyah from 51 schools/madrasas in 4 districts and 1 city, namely Sleman Regency, Kulon Progo Regency, Bantul Regency, Gunung Kidul Regency, and Yogyakarta City. Data analysis used descriptive statistics which were then converted into 4 categories. The results of the average number of scores (X) amounted to 130.64, which is in category B (Good). This means that the teacher's ability to understand LVE-based sex education is good and has the awareness to implement it.